Time trends in neural tube defects prevalence in relation to preventive strategies: an international study. Issue 10 (1st October 1999) - Rosano, A; Smithells, D; Cacciani, L; Botting, B; Castilla, E; Cornel, M; Erickson, D; Goujard, J; Irgens, L; Merlob, P; Robert, E; Siffel, C; et al.
Abstract : OBJECTIVE: To examine time trends in neural tube defects (NTD) prevalence from 1987 to 1996 in relation to the primary prevention policies for folic acid supplementation strategies in different countries. DESIGN: Retrospective time trends analysis of NTD prevalence. SETTING: 11 birth defect registries of congenital malformations participating in the International Clearinghouse for Birth Defects Monitoring System, in the period from 1 July 1987 to 30 June 1996. SUBJECTS: 8207 live births, stillbirths and terminated pregnancies affected by anencephaly or spina bifida registered by the 11 participating centres 1987-1996. OUTCOME MEASURES: Prevalence rate ratios based on the annual rates, using the Poisson regression model. RESULTS: During the study period a significant fall in prevalence rates for all NTD is present in Atlanta (USA), England and Wales, Hungary and Japan, and a significant rise in Norway and South America. After adjusting for the secular trends observed in the earlier years of the study, no significant trend can be attributed to preventive strategies. Data on NTD prevalence are supplemented with information on folate awareness among some of the populations studied. CONCLUSION: There is no evidence that, up to the middle of 1996, any change in time trend was attributable to the introduction of national folate supplementation policies. The possible effectiveness of folate supplementation policies for the reduction of NTD clearly needs to be tried and studied for several more years. Considering that in the Western world about 50% of pregnancies are unplanned, a policy that rests on action taken before conception can only have limited success. Strategies based on food enrichment, such as was introduced in the USA from the beginning of 1998, may prove to be more successful.